Muscle Wasting and Resistance of Muscle Anabolism: The “Anabolic Threshold Concept” for Adapted Nutritional Strategies during Sarcopenia - Dominique Dardevet; Didier Rémond; Marie-Agnès Peyron; Isabelle Papet; Isabelle Savary-Auzeloux; Laurent Mosoni (The Scientific World Journal)
Skeletal muscle loss is observed in several physiopathological situations. Strategies to prevent, slow down, or increase recovery of muscle have already been tested. Besides exercise, nutrition, and more particularly protein nutrition based on increased amino acid, leucine or the quality of protein intake has generated positive acute postprandial effect on muscle protein anabolism. However, on the long term, these nutritional strategies have often failed in improving muscle mass even if given for long periods of time in both humans and rodent models. Muscle mass loss situations have been often correlated to a resistance of muscle protein anabolism to food intake which may be explained by an increase of the anabolic threshold toward the stimulatory effect of amino acids. In this paper, we will emphasize how this anabolic resistance may affect the intensity and the duration of the muscle anabolic response at the postprandial state and how it may explain the negative results obtained on the long term in the prevention of muscle mass. Sarcopenia, the muscle mass loss observed during aging, has been chosen to illustrate this concept but it may be kept in mind that it could be extended to any other catabolic states or recovery situations.